PJMHS 2022
DOI: 10.53350/pjmhs22166476
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect Pender's Model in Changing Employees' Eating Behaviors Suffer Hypertension at Mosul University Iraq

Abstract: Background: Hypertension is the most common risk factor for cardiovascular disease (CVD) , and it frequently coexists with other CVD risk factors and bad lifestyle behaviors such smoking, diabetes, cholesterol, obesity, lack of physical activity, and a poor diet. The objective of the article to identify the assessing the effect Pender's Model in changing employees' eating behaviors suffer hypertension at Mosul University Iraq. Method: A descriptive Cross-sectional design by using approach is conducted to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…This study is compatible with the results of a previous study (7) .The results of the study indicated that the majority of the participants were female (55%). These findings are compatible with other findings from a number of previous studies (8)(9)(10)(11)(12)(13) . This could be because there were more women than men over 50, some of whom were widowed, overweight or obese and had a low level of education.…”
Section: Discussionsupporting
confidence: 93%
“…This study is compatible with the results of a previous study (7) .The results of the study indicated that the majority of the participants were female (55%). These findings are compatible with other findings from a number of previous studies (8)(9)(10)(11)(12)(13) . This could be because there were more women than men over 50, some of whom were widowed, overweight or obese and had a low level of education.…”
Section: Discussionsupporting
confidence: 93%
“…The study included 62 male and female nurses working in the field of neonatal care in hospitals in the city of Mosul and it turns out that a large proportion of them were males within the limits of (80.65%), while women were (19.35%), and the average gender was (1.21), that is, they were dominated by the proportion of males. As for the ages of the sample participating in the study, it was (30.43), that is, they are the youth category and there was a clear effect regarding the educational level, This study similar with others study in Iraq (5)(6)(7)(8)(9)(10)(11) , who found this male more than female and mean age between (28-31 years).Comparison between (Pre test study) and (Pre test control), comparison between (Post1 test study) and (Post1 test control) and comparison between (Post2 test study) and (Post2 test control).There are no significant differences between (Pre test study) and (Pre test control) , there are significant differences between (Post1 test study) and (Post1 test control) and there are significant differences between (Pos2 test study) and (Pos2 test control) . The study sample before starting the program did not have any information related to the practical aspect of phototherapy, but when giving the program and after the second test, the results were clearly shown, there are very significant significant differences 12 .…”
Section: Discussionsupporting
confidence: 84%
“…The direct and indirect financial costs of treatment, as well as its qualitative and human costs, can also be exacerbated by violence at work. These costs include, but are not limited to, loss of efficiency, absenteeism, loss of expertise, the effect on the morale of workers, issues with the organization's or the institution's image, and a reduction in the safety and well-being of employees and patients (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…"From 2002 to 2013, incidents of serious workplace violence (those requiring days off for the injured worker to recuperate) were four times more common in healthcare than in private industry on average. In 2013, the broad healthcare and social assistance" (36)(37)(38)(39)(40)(41)(42) .…”
Section: Discussionmentioning
confidence: 99%